South Africa : Financial Sector Assessment Program-Financial Safety Net, Bank Resolution, and Crisis Management Framework-Technical Note. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses recommendations made during the Financial Sector Assessment Program (FSAP) for South Africa in the areas of contingency planning, crisis management, and bank resolution. The proposed scope of the new resolution regime and of the South African Reserve Bank's (SARB) jurisdiction as the resolution authority remains unclear. It is suggested that authorities should consider focusing on all deposit-taking institutions and only those other financial institutions that are currently deemed systemic. Non-deposit-taking financial institutions that are not found to be systemic should be resolved by the Prudential Authority or the Market Conduct Authority, whichever is the lead regulator.